1995
DOI: 10.1016/0378-1097(95)00087-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient nitrogen and manganese on manganese peroxidase and laccase production by Lentinula (Lentinus) edodes

Abstract: Lentinula (Lentinus) edodes, strain LS4, produces manganese‐dependent peroxidase (MnP) and laccase, but not lignin peroxidase, when grown on a defined medium with glucose as sole carbon source. MnP production is suppressed by nitrogen whereas highest levels of laccase were observed when the fungus was grown under high nitrogen (26 mM) conditions. Both the titre and time of appearance of MnP were affected by the concentration of Mn in the culture medium with highest enzyme levels recorded in cultures supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
111
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 0 publications
6
111
0
7
Order By: Relevance
“…The xylanase and cellulase activities of all soil suspension samples were determined by reference to a standard curve produced with purified endoxylanase from Thermobacillus xylanilyticus (Debeire-Gosselin et al 1992) and commercial cellulase (322 U ml -1 , endo-b-glucanase purified from Aspergillus niger, Megazyme) at concentrations ranging between 0.01 and 0.1 U ml -1 for the cellulase and between 0.001 and 0.01 mU ml -1 for xylanase, both in sodium acetate buffer (50 mM, pH 5). Laccase activity was assayed as described by Buswell et al (1995), Floch et al (2007. One hundred milliliters of 0.55 mM laccase substrate (ABTS, 2,2 0 -azinobis-3-ethylbenzothiazoline-6-sulfonic acid diammonium salt, Sigma) was prepared by using sodium acetate buffer (50 mM, pH 4.5) followed by vigorous shaking with a magnetic stirrer.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…The xylanase and cellulase activities of all soil suspension samples were determined by reference to a standard curve produced with purified endoxylanase from Thermobacillus xylanilyticus (Debeire-Gosselin et al 1992) and commercial cellulase (322 U ml -1 , endo-b-glucanase purified from Aspergillus niger, Megazyme) at concentrations ranging between 0.01 and 0.1 U ml -1 for the cellulase and between 0.001 and 0.01 mU ml -1 for xylanase, both in sodium acetate buffer (50 mM, pH 5). Laccase activity was assayed as described by Buswell et al (1995), Floch et al (2007. One hundred milliliters of 0.55 mM laccase substrate (ABTS, 2,2 0 -azinobis-3-ethylbenzothiazoline-6-sulfonic acid diammonium salt, Sigma) was prepared by using sodium acetate buffer (50 mM, pH 4.5) followed by vigorous shaking with a magnetic stirrer.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Some species, like the well-studied Phanerochaete chrysosporium, present laccase activity only when nitrogen concentration falls to limiting levels (10,12,15). On the other hand, L. edodes exhibits decreasing laccase activity following the depletion of nitrogen (3,15). The culture media used in the present study was efficient to stimulate laccase activity in L. sordida with the nitrogen sources used ammonium phosphate (0.15 g/L), yeast extract (0.1 g/L) and ammonium molibdate (0.011 g/L).…”
mentioning
confidence: 99%
“…Kim et al [66] demonstrated the presence of H 2 O 2 dependent enzyme activity to declourize the dye Brilliant Blue R by the fungus Pleurotus ostreatus. Buswell et al [67] reported that the production of the extracellular ligninolytic enzymes is strongly affected by the nature and amount of the nutrients, especially nitrogen (N) and microelements, in the growth substrate. The basidiomycetous fungus Ganodermaa lucidum has been found positive for the removal of Rhodamine-B and Sandolan rhodine dyes.…”
Section: Mechanism Of Dye Degradationmentioning
confidence: 99%